Dialogue gap : why communication isn't enough and what we can do about it, fast. - Nixon, Peter (Singapore : John Wiley & Sons, 2012)
The book that bridges the chasm between communication and understanding in negotiations For years Peter Nixon worked with people from all walks of life, teaching them the art of negotiation. But it soon became apparent that the issue was not negotiation itself, but dialogue between parties. We have become experts at sending information-via email, text message, Internet, TV, and other forms of media, communicating, but not engaging, in an active dialogue defined by collaborative thinking. In Dialogue Gap, Nixon explores this growing disconnect and its significance in an increa.
pt. 1. Dialogue Gap -- pt. 2. Dialogue Solutions -- pt. 3. Dialogue Leadership.
Includes bibliographical references and index.
English.
John Wiley and Sons
Keywords: Interpersonal communication; Oral communication; Business communication; Communication interpersonnelle; Communication orale; Communication dans l'entreprise.; BUSINESS & ECONOMICS -- Negotiating; Business communication; Interpersonal communication; Oral communication